Illustrating the Intercultural in Portuguese Secondary School Foreign Language (FL) Classrooms - Ulisses, Carla (2017)
This article reports on a small-scale action research project developed in the context of the practicum of a Teacher Education Masters course at the Faculty of Letters, the University of Porto. The project was focussed on the importance of visual stimuli in the foreign language teaching classroom (English and Spanish), within the context of an intercultural approach. Different strategies, activities and materials were employed with the general aim of helping the learners to develop their critical cultural awareness. The learners played a central role, participating actively, by bringing into the classroom their own knowledge of the world. Simultaneously, the role of the teacher was not without importance in this action research project, presenting herself as an example of a cultural mediator.